Applications of systems thinking in integrated solid waste management planning for African cities: the case of Nairobi, Kenya - Kasozi, A (Department of Chemical Engineering, 2014)
The majority of solid waste generated by urban living cannot be assimilated in the city environment,and initial improvements in urban cleanliness and health were only realized when organized wastecollection and disposal outside of city limits was introduced in Europe in the late 19th century.Sanitary landfills were later invented to reduce the environmental effects of large unsecureddumpsites, it is now however increasingly being shown that this too as a waste management strategyoffers a worse environmental footprint than material and energy recovery and recycling (Cherubini et01., 2009). Modern approaches to solid waste management, collectively referred to as Integrated Solid Waste Management (ISWM), therefore increasingly incorporate strategies to reduce wastegeneration and to encourage re-use and recycling of materials, and recovery of energy; with landfilling as a last option for residual waste. This represents a shift in waste management paradigmsfrom a focus on collection for disposal, to an increasing integrated interest in the entire waste chainfrom waste generation to material and energy recovery and recycling, and to safe residual treatmentand disposal. The increasing acceptance of Mebratu's (1998) cosmic interdependence model as amore realistic conceptualisation of our world and how its natural, social, and economic spheresinteract however implies that sustainable waste management design needs to take a further leapinto a systems discourse, and cannot be considered in isolation of a rigorous understanding of thesystemic interactions of the social and economic circumstances unique to particular areas. This callsfor a greater understanding of how ISWM principles fit within the social and economic contexts ofgiven areas; an analytical gap that can be filled through the use of systems thinking and systemsbasedtools to multi-dimensionally investigate, and articulate the structures and relationships thatoften underlie complex situations. While systems thinking has found wide application in thesustainability sciences as a prerequisite to building truly sustainable systems (for example Capra,2002 and Hjorth & Bagheri, 2006), it has as yet found little application in waste management analysisand designs, which have evolved from simple problem-oriented to ""integrated"" engineeringmethods. In response to dire solid waste conditions in Nairobi, the government of Kenya agreed in 2009 tocollaborate with UNEP to develop an ISWM Strategy for Nairobi. The project was initiated in March2009, and a National Task Team was established to oversee the development of the plan along with ateam from the University of Cape Town, of which the author was part. The core elements of theresulting Nairobi City ISWM Strategy (CCN & UNEP, 2010) were finalised in April 2010 and included,alongside the formal use of the UNEP ISWM planning methodology, some application of systemsanalysis. These systems analyses could however only be partially developed due to project deliverytime constraints, and this dissertation extends these analyses to completion and explores theirimplications for ISWM in Nairobi.Systems based tools from the research area of system dynamics were applied to systematicallystructure the waste problem and situation in Nairobi, and to develop conceptual causal loop modelsarticulating the solid waste system in Nairobi as a whole. This enabled the highlighting of inherentwaste system strengths and weaknesses in Nairobi, system drivers, leverage points, behaviouralarchetypes, and resulting implications for ISWM planning in Nairobi. The insights generated wereused to inform an examination of whether the intervention strategies finally developed in theNairobi ISWM Strategy Plan (CCN & UNEP, 2010) were adequate at a fundamental level andsufficiently relevant. It was also determined that the bulk of Nairobi's solid waste is organic, and thatthe material recycling and reuse capacity in the city is a key system driver in its waste management towards ISWM, of which organic waste valorization comprises a significant part. It was therefore ofinterest to determine the current capacity, and potential for expansion of organic waste valorizationin the city towards amplifying material recycling as a system driver towards ISWM.The application of a systems based analysis of Nairobi's waste management identified the presenceof ten system drivers of varying nature and flexibility, through which to influence the achievement ofISWM objectives in the city. Potential system leverage points in Nairobi's waste sector were alsoidentified and allowed the development of additional systemic interventions through which largewaste sector changes towards ISWM may be achieved with relatively small inputs. The solid wastemanagement scene in Nairobi was also found to involve a combination of two systems archetypes asdefined by Braun (2002): a 'Success to the successful' trend of private waste collection relative to theCity Council, embedded within a larger 'Tragedy of the Commons' trend - the commons being thecity's economic, human, and natural capital; and implicitly its potential revenue base for collectionservice providers, whose tragic diminishing for all will be the inevitable result if the current operationand disposal practices of both the private collectors and the City Council continue. The interventionsproposed in the Nairobi ISWM Strategy (CCN & UNEP, 2010) were found to have targeted many ofthe fundamental causes leading to the current solid waste situation in Nairobi, due in part to thepartial use of systems analysis in their development by the author; additional insights were howevergenerated from the completed systems analysis discussed in this dissertation. These highlight a needfor the development of policy consistent with eight extra systemic interventions, six of which may beconsidered critical to the success of ISWM efforts in Nairobi.The latter focus on the potential of organic waste valorization to amplify Nairobi's material recyclingcapacity as a waste system driver towards ISWM revealed that there is a leakage of 14% to 23% of allwaste in the city due to organic waste degradation at open dumps or collection points. There is acurrent interest in the use of such organic wastes as animal feed in Nairobi City, and this userepresents a promising but seemingly under tapped organic waste valorisation potential that is likelyto gain in importance in future. Bulk compost production from organic waste is uneconomical underthe present market conditions in the city, and does not currently offer a rational option for the bulkvalorisation of organic wastes in Nairobi. The anaerobic digestion of organic waste for energyhowever shows potential to achieve radically improved organic waste valorisation levels in the city,and from techno-economic modelling undertaken of potential medium scale biogas-to-energy plantinvestments, seems feasible at the current biogas energy feed-in tariffs of 6 KShs/kWh (17-19 US Cents/kWh) and an organic waste tipping fee of KShs. l/kg organic wastetreated, is recommended to achieve more attractive investment payback periods of under five yearsfor especially private investors, and generally agrees with feed-in tarif